Resposta motora em larvas de Zebrafish expostas previamente à um tratamento crônico com dopamina - Ana Carolina Monteiro de Souza Lima (2016)
The early stages of neurodevelopment are crucial to the normal development of the brain. Alterations during neurodevelopment can lead to behavioral and physiological alterations in adult life, which can be associated to schizophrenia and attention deficit hyperactivity disorder (ADHD). Both schizophrenia and ADHD present changes in dopaminergic signaling and development. It is known that dopaminergic system is expressed early in neurodevelopment. This way, it is important to establish models for the understanding of the bases of these etiologies. The zebrafish has been growing as a strong experimental model due to your relative similarity to humans, external development and easy pharmacological manipulation. To test if our hypothesis that dopamine has role on the development of motor behavior, we used zebrafish as our experimental model. Our work had the objective to investigate if the motor behavior alterations and the dopaminergic behavioral response, caused by the increase of the dopamine levels on the developmental window between the 3rd and 5 day post fertilization (dpf), are sustained in larvae in advanced age. Zebrafish larvae were chronically treated from the 3rd to 5 dpf and, at the ages of 5, 7 and 14dpf they were analyzed to evaluate their motor behavior, with and without additional pharmacological challenge with dopamine, SKF-38393 or quinpirole. We analyzed distance travelled, mean speed, time mobile and mobile episodes during 5 and 30 minutes with the intention of implying the influence of DARPP-32 and Akt signaling, respectively. In our results, it was possible to conclude that: 1) the increase of dopamine between 3-5dpf alters the locomotion of larvae; 2) the alteration of some motor parameters is sustained until advanced ages; 3) the main behavioral alterations occurred during 30 minutes analyzes, suggesting that the signalization by the Akt pathway is more affect by the chronic treatment with dopamine. It was possible to conclude that the dopaminergic signaling has a role on the development of the locomotor activity of the zebrafish larvae.